Abundance and population structure of Crocodylus acutus (Reptilia: Crocodylidae) in Palmasola lagoon, Oaxaca, Mexico - García-Grajales, Jesús; Buenrostro Silva, Alejandra (Revista de Biología Tropical, 2014)
Abundance and population structure are important parameters to evaluate and compare the conservation status of a population over time in a given area. This study describes the population abundance and structure of Crocodylus acutus in Palmasola lagoon, Oaxaca. The field works consisted of night surveys during the new moon phase, between the 21:00 and 24:00h. These were conducted during the dry and wet seasons and counted the number of individuals to obtain population estimates. Recorded encounter rates ranged from 32 to 109.3ind./km in 40 journeys deployed with an average time of 18 minutes browsing. The estimated population size using the Messel´s model ranged from 32.7 to 93 individuals. For both seasons, there was a marked dominance of subadults, followed by juveniles and to a lesser extent adult individuals, as well as undetermined individuals (i.e. unknown body/size/length), in both seasons. There was also a significant association with mangrove areas (26.1%) by juveniles; the subadults´s individual use of superficial water (22.7%) and mangrove areas (15.7%); meanwhile the adults were observed on superficial water (9.7%). This information contributes to our understanding of the population ecology of C. acutus in the Palmasola lagoon where the estimated population size seems to show higher values when compared to other reports in the country.